Reengineering the Romanian timber supply chain from a process management perspective - Rauch, Peter (Array, 2019)
Implementation of process management in the forest supply chains has a great potential for organizational and managerial improvement, at least by resource saving. Nevertheless, techniques of process management have been scarcely used to improve the forest supply chains in many parts of the world. In this study, for both Romanian state and private forests, the processes of the timber supply chain – from the harvest site to the forest-based industry plant – are mapped and analyzed. The main objectives of this work were to identify process optimization potentials and to redesign processes in order to improve the performance of the Romanian timber supply chain. Results show that particularly inter-organizational processes offer great saving potentials, mainly due to the existing multi-level hierarchy and multi-level control obligations. Therefore, introducing a web-based platform to enhance a collaborative workflow can considerably decrease the time needed for providing harvest sites or logs to customers via auctions. Further process optimization can be reached by the empowerment of lower level hierarchies facilitating the reduction of hierarchy levels of involved state organizations.